THE BIRD IN THE HAND FALLACY AND AGENCY PROBLEMS: A COMPARATIVE ANALYSIS - Binod Shah; Kiran Kumari Sah; Rajesh Kumar Sah (Journal of Learning on History and Social Sciences, 2024)
Through the conduction of comparative and comprehensive analysis of relevant data, literature review, and empirical evidence, this paper aims to apply to decision making and reasoning, the fallacy occurs when someone overvalues a sure thing, even when the potential benefits of an alternative option are significantly higher and more probable. Conversely, the agency problem, arising from conflicts of interest between managers and shareholders, can influence dividend decisions in ways that prioritize managerial interests over shareholder value maximization. The findings highlight significant influences of both the "bird in the hand" fallacy and the agency problem on dividend policy. However, their implications and the strategies to mitigate their effects vary significantly. The "bird in the hand" fallacy, rooted in a preference for certainty, tends to lead investors to favour immediate dividends over potentially higher future gains from reinvestment which may not materialize. The methodology employed in this study includes a descriptive analysis research design. Literature review is to establish theoretical foundations and empirical analysis is to substantiate these theoretical keystones. By examining historical data, the study aims to provide insights into how these factors shape corporate dividend policies and investor behaviour. Ultimately, the research underscores the importance of balancing short-term dividend pay-outs with long-term growth opportunities. It suggests that effective dividend policy should consider both investor preferences for current income and the potential benefits of reinvestment in enhancing future shareholder value. By understanding these dynamics and implementing appropriate strategies, firms can navigate the complexities of dividend policy to achieve sustainable financial performance and shareholder satisfaction